Evidence that PrfA, the pleiotropic activator of virulence genes in Listeria monocytogenes, can be present but inactive. - Renzoni, A (1997)
All virulence genes of Listeria monocytogenes identified to date are positively regulated by PrfA, a transcriptional activator belonging to the Crp-Fnr family. Low temperature and cellobiose are two environmental signals known to repress expression of virulence genes in L. monocytogenes. In the present work, we analyzed the effect of temperature and cellobiose on the expression of the PrfA protein. At low temperature, PrfA was undetected, although prfA monocistronic transcripts are present. In contrast, PrfA was fully expressed in the presence of cellobiose. These results strongly suggest that virulence gene activation depends on both the presence of PrfA and additional regulatory pathways that either modify PrfA or act synergistically with PrfA.